Snapshot on drug‐resistance rate and profiles in patients with chronic hepatitis B receiving nucleos(t)ide analogues in clinical practice. Issue 6 (12th April 2013) - Salpini, R.; Alteri, C.; Cento, V.; Pollicita, M.; Micheli, V.; Gubertini, G.; De Sanctis, G.M.; Visca, M.; Romano, S.; Sarrecchia, C.; Andreoni, M.; Angelico, M.; et al.
Abstract: While the selection of complex HBV drug‐resistance patterns on therapeutic failure can compromise the efficacy of anti‐HBV therapies, recent data show that patients failing treatment without drug‐resistance have a rate of virological success close to drug‐naive patients. The goal of this study is defining, in clinical practice, the burden of drug‐resistance mutations in a cohort of patients treated with anti‐HBV drugs. Prevalence and patterns of drug‐resistance were analyzed by RT‐sequencing in 204 patients infected chronically: 148 experiencing virological rebound (defined as an increase in serum HBV‐DNA > 20 IU/ml after achieving virological success [HBV‐DNA < 20 IU/ml]), and 56 null/partial responders (always detectable serum HBV‐DNA [>20 IU/ml] within 48 weeks of therapy). The highest rate of drug‐resistance was observed in patients experiencing virological rebound (prevalence, 79.1%). Conversely, almost half (46.4%) null/partial responders have no evidence of drug‐resistance. The rate of drug‐resistance was higher in patients treated with lamivudine (76.8% [109/142]) and telbivudine (83.3% [5/6]), followed by adefovir (62.5% [15/24]), and entecavir (52.2% [12/23]). Complex mutational patterns characterized by the co‐presence of rtM204V/I‐rtA181T/V (impairing the efficacy of all anti‐HBV drugs) were detected in four patients (2.7%) with virological rebound. Drug‐resistance is the main cause of failure to therapy in patients experiencing virological rebound, supporting the need of rapid switch to anti‐HBV drugs with higher genetic barrier and potency (entecavir/tenofovir). Conversely, nearly half of null/partial responders shows no evidence of drug‐resistance mutations, maintaining high chance of achieving therapeutic success with the same class of drug. In this setting, genotypic resistance may help in selecting patients still carrying wild‐type viruses, that may take major benefits from antiviral treatment. J. Med. Virol. 85: 996–1004, 2013. © 2013 Wiley Periodicals, Inc.